The social order of markets - Jens Beckert (Max Planck Institute for the Study of Societies, 2007)
In this article I develop a proposal for the theoretical vantage point of the sociology of markets, focusing on the problem of the social order of markets. The initial premise is that markets are highly demanding arenas of social interaction, which can only operate if three inevitable coordination problems are resolved. I define these coordination problems as the value problem, the problem of competition and the cooperation problem. I show that these problems can only be resolved based on stable reciprocal expectations on the part of market actors, which have their basis in the socio-structural, institutional and cultural embedding of markets. The sociology of markets aims to investigate how market action is structured by these macrostructures and to examine the change of institutions, networks and cultural frames of market action.
Keywords: 300; Marktmechanismus; Soziale Beziehungen; Wirtschaftssoziologie; Theorie